Pengaruh Bentuk Butiran Terhadap Kekuatan Tanah Pasir - Frimadofi Frimadofi; Muhamad Yusa; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
There are many factors that affect the sands shear strength. One of the most important factors is the shape of the sand grains. The shape of sands in nature varied greatly, from angled to rounded. Natural sands from the river is usually rounded, while the sands from stone crusher is usually angular. The sands that is expected to be rounded in shape comes from the Kampar River and the sands is expected to have an angular shape from Kota Kijang quarry. In this research, the shape of sand grains were captured using a specified smartphone camera. The image then were analyzed using Image-j software. Direct shear test was carried out on various relative density of dry sands (loose and dense condition). Image analysis shows that Kampar’s sand is sub-rounded, while Kijang’s sand is sub-angular. The value of internal friction angle (ϕ) sub-angular sand is 14% greater in dense conditions and 8.7% greater in loose conditions than for sub-rounded sand. The value of internal friction angle (ϕ) is based on relative density (Dr) in dense conditions greater than 6.3% among fellow sub-angular sands. The value of internal friction angle (ϕ) is based on relative density (Dr) in loose conditions greater than 0.5% among fellow sub-rounded sands.Keywords : Sand, the shape of grain, image-j software, relative density (Dr), shear strength, direct shear test.